Influence of injection mode on transport properties in kilometer‐scale three‐dimensional discrete fracture networks. Issue 9 (12th September 2015) - Hyman, J. D.; Painter, S. L.; Viswanathan, H.; Makedonska, N.; Karra, S.
Abstract We investigate how the choice of injection mode impacts transport properties in kilometer‐scale three‐dimensional discrete fracture networks (DFN). The choice of injection mode, resident and flux‐weighted, is designed to mimic different physical phenomena. It has been hypothesized that solute plumes injected under resident conditions evolve to behave similarly to solutes injected under flux‐weighted conditions. Previously, computational limitations have prohibited the large‐scale simulations required to investigate this hypothesis. We investigate this hypothesis by using a high‐performance DFN suite, dfnWorks, to simulate flow in kilometer‐scale three‐dimensional DFNs based on fractured granite at the Forsmark site in Sweden, and adopt a Lagrangian approach to simulate transport therein. Results show that after traveling through a pre‐equilibrium region, both injection methods exhibit linear scaling of the first moment of travel time and power law scaling of the breakthrough curve with similar exponents, slightly larger than 2. The physical mechanisms behind this evolution appear to be the combination of in‐network channeling of mass into larger fractures, which offer reduced resistance to flow, and in‐fracture channeling, which results from the topology of the DFN.